Proceso de atencion de enfermeria con neuroartropatia de charcot en pie diabetico: estudio de caso - Calderon Vivanco, Mercedes Carolina; Chapa Tinoco, Karen Alejandra (Machala : Universidad Técnica de Machala, 2019)
Charcot neuropathy is a progressive disease and is among the most common complications that occur in the diabetic foot of a person with diabetes mellitus, which can become a functional and physical limitation of the foot creating medical concerns. Charcot's foot is a degenerative disease of neuromuscular origin, which appears in a short period of time; When the patient comes to present a minor injury or sprain of the foot and ankle, this will generate a serious mismatch of the anatomy of the foot. Because patients with diabetes mellitus do not have good vascularization and a rise in sugar levels, it will cause damage to the nervous system thereby increasing the partial or total loss of pain, causing weakening of the bones and creating minor dislocations or trauma . This degenerative arthropathy predominates 0.8 to 7.5% in the diabetic population regardless of gender, according to the World Health Organization there are 1 of 680 patients with type 1 diabetes who have generated this arthropathy; in the most severe cases, the committed member will be mutilated; That is why a timely and accurate diagnosis is necessary to avoid this complication. In America, due to its number of inhabitants, the US is the country with the highest prevalence of 1 to 6% among 16 million inhabitants who have the disease, while in Colombia a single epidemiological study was carried out that reported the proportions of the affected sex that agrees with the world In the neighboring country Peru does not have epidemiological data to identify the incidence that this disease would occur. In Ecuador, no studies or epidemiological data on the disease have been taken to establish an exact prevalence, although there are clubs that deal with diabetes from public and private hospitals; There are no studies on the nationwide statistics of Charcot's neuroarthropathy.
La neuropatía de Charcot es una enfermedad progresiva y se encuentra entre las complicaciones más usuales que se dan en el pie diabético de una persona con diabetes mellitus, la cual puede llegar a ser una limitación funcional y física del pie creando preocupaciones médicas. El pie de Charcot es una enfermedad degenerativa de origen neuromuscular, que aparece en un periodo corto de tiempo; cuando el paciente llega a presentar una lesión menor o esguince de pie y tobillo, esto generará, un grave desajuste de la anatomía del pie. Debido a que los pacientes con diabetes mellitus no presentan una buena vascularización y un alza en los niveles de azúcar, ocasionará daños en el sistema nervioso aumentando así la pérdida parcial o total del dolor, provocando la debilitación de los huesos y creando luxaciones o traumatismos menores. Esta artropatía degenerativa predomina un 0.8 al 7.5% en la población diabética sin distinción de género, según la Organización Mundial de la Salud existen 1 de 680 pacientes con diabetes tipo 1 que han generado esta artropatía; en los casos más severos se procederá a la mutilación del miembro comprometido; por eso es necesario un diagnóstico oportuno y certero para evitar esta complicación. En América, por su cantidad de habitantes, EEUU es el país con mayor prevalencia del 1 al 6% entre 16 millones de habitantes que posee la enfermedad mientras que en Colombia se realizó un único estudio epidemiológico que reportó las proporciones del sexo afectado que concuerda con la mundial. En el país vecino Perú no cuenta con datos epidemiológicos para identificar la incidencia que se daría esta enfermedad. En Ecuador, no se han realizado estudios o se han sacado datos epidemiológicos sobre la enfermedad para poder establecer una prevalencia exacta, a pesar que existen clubes que tratan sobre la diabetes son de hospitales públicos y privados; no hay estudios sobre la estadística a nivel nacional de la neuroartropatía de Charcot.
Keywords: NEUROPATIA DE CHARCOT; PIE DIABETICO; NEUROMUSCULAR; TRAUMATISMOS